2018
DOI: 10.1038/s41598-018-22959-6
|View full text |Cite
|
Sign up to set email alerts
|

Sites associated with Kalydeco binding on human Cystic Fibrosis Transmembrane Conductance Regulator revealed by Hydrogen/Deuterium Exchange

Abstract: Cystic Fibrosis (CF) is caused by mutations in the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR). Mutations associated with CF cause loss-of-function in CFTR leading to salt imbalance in epithelial tissues. Kalydeco (also called VX-770 or ivacaftor) was approved for CF treatment in 2012 but little is known regarding the compound’s interactions with CFTR including the site of binding or mechanisms of action. In this study we use hydrogen/deuterium exchange (HDX) coupled with mass spectrometry to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 71 publications
(96 reference statements)
4
25
0
Order By: Relevance
“…Because the channel opening rate shows greatest temperature sensitivity (47, present study), the data suggest that the principal effect of ivacaftor is to promote channel opening, particularly at temperatures Յ30°C. Integrating these data with biochemical and structural data, which demonstrated that ivacaftor reduces thermal stability (12,49) and increases conformational flexibility (21), argues that ivacaftor exerts its effects by destabilizing a closed channel conformation. In addition, loss of the temperature dependence of channel gating suggests that ivacaftor might modify the irreversible cyclic gating scheme of CFTR to favor a reversible one.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because the channel opening rate shows greatest temperature sensitivity (47, present study), the data suggest that the principal effect of ivacaftor is to promote channel opening, particularly at temperatures Յ30°C. Integrating these data with biochemical and structural data, which demonstrated that ivacaftor reduces thermal stability (12,49) and increases conformational flexibility (21), argues that ivacaftor exerts its effects by destabilizing a closed channel conformation. In addition, loss of the temperature dependence of channel gating suggests that ivacaftor might modify the irreversible cyclic gating scheme of CFTR to favor a reversible one.…”
Section: Discussionmentioning
confidence: 98%
“…Using hydrogen/deuterium exchange mass spectroscopy, Byrnes et al (12) investigated ivacaftor binding to a human CFTR construct with thermostabilizing mutations that themselves modify CFTR channel gating (4,57). Intriguingly, ivacaftor bound to multiple sites on this CFTR construct, including the Lasso motif (80), transmembrane segment 2 in MSD1, the coupling helices of intracellular loops 1, 3, and 4, and NBD2 with the tightest binding located at the MSD2-NBD1 and MSD2-NBD2 interfaces (12). These data suggest that ivacaftor might bind near F508 in a region overlapping the small molecule-binding sites identified by Kalid et al (41) at the interface of the NBDs with the MSDs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been proposing the putative binding site for ivacaftor by distinct methods. Some initial reports indicated that ivacaftor might bind to a region of amino acids at the NBD1/2 interface and the coupling helix of intracellular loop 1 (Veit et al, 2014) and/or the 'ball-and-socket' joint close to intracellular loop 4 (Byrnes et al, 2018). More recent studies provided direct evidence of the binding site of ivacaftor at the interface between TMDs by using electron cryomicroscopy and electrophysiological assays (Liu F. et al, 2019;Yeh et al, 2019).…”
Section: Potentiators: Restoring the Channel Gating And Conductancementioning
confidence: 99%
“…We showed previously that the channel activity of detergent purified CFTR was potentiated by 311 ivacaftor (VX-770) following its reconstitution into liposomes, supporting the claim that VX-770 312 acts via direct binding to CFTR (Eckford, Li et al 2012). Another group recently studied the 313 interaction of VX-770 with detergent solubilized CFTR using hydrogen/deuterium exchange 314 (Byrnes, Xu et al 2018). This method showed that there were multiple regions in CFTR that 315 underwent changes in conformation after VX-770 interaction; however, the specific drug binding 316 site has yet to be defined.…”
mentioning
confidence: 99%